Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have this equation: $$\boxed{\cos(2x) - \cos(8x) + \cos(6x) = 1}$$


RIGHT

And its right solution from the textbook is: $$ \begin{align} \cos(2x)+\cos(6x)&=1+\cos(8x)\\\\ 2\cos(4x)*\cos(2x)&=2\cos^2(4x)\\\\ \cos(4x)*(\cos(2x)-\cos(4x))&=0\\\\ \cos(4x)*2\sin(3x)*\sin(x)=&0 \end{align} $$

  1. $\cos(4x) = 0 \implies 4x = \frac{\pi}{2} + \pi k \implies \boxed{x=\frac{\pi}{8} + \frac{\pi k}{4}}$
  2. $\sin(3x) = 0 \implies 3x = \pi k \implies \boxed{x=\frac{\pi k}{3}}$
  3. $\sin(x) = 0 \implies \boxed{x=\pi k}$

WRONG

And this is the way how I have been tried to solve it (with different approach) and here I need a help to determine where I'm wrong: $$ \begin{align} \cos(2x) - \cos(8x) + \cos(6x) &= 1\\ \cos(2x) + \cos(6x) &= 1 + \cos(8x) \end{align} $$

Then using this formula:

$$\bbox[Beige]{\boxed{\cos\alpha + \cos\beta = 2\cos(\frac{\alpha + \beta}{2}) \cos(\frac{\alpha - \beta}{2})}} \tag{1}$$

$$2\cos(4x)\cos(2x) = 1 + \cos(8x)$$

And then similarly:

$$\bbox[Beige]{\boxed{\cos2\alpha=2\cos^2\alpha-1}} \tag{2}$$

$$2\cos(4x)\cos(2x) = 1 + 2\cos^2(4x) - 1$$

After that I subtracted $1$ from $1$ in the right part and divided both right and left parts by $2$:

$$\cos(4x)\cos(2x) = \cos^2(4x)$$

Then once again I divided both parts. This time by $\cos(4x)$ and with the aim not to lose a root I checked whether $\cos(4x)$ can be equal to zero.

$$\cos(4x) = 0 \implies 4x = \frac{\pi}{2} + \pi k \implies \boxed{x=\frac{\pi}{8} + \frac{\pi k}{4}}$$

so here I found the first root. And using formula (2):

$$\cos(2x) = \cos(4x) \implies \cos(2x) = 2\cos^2(2x) - 1$$

then I simply introduced new variable and solved quadratic equation:

$$u = \cos(2x)$$ $$ 2u^2 - u -1 = 0\\ u_1=1, \, u_2=-\frac{1}{2} $$

So finally:

  1. $\cos(2x) = 1 \implies 2x = \pi k \implies \boxed{x=\frac{\pi k}{2}}$ (wrong)
  2. $\cos(2x) = -\frac{1}{2} \implies 2x = \pm \frac{2 \pi}{3} + 2\pi k \implies \boxed{x=\frac{\pi}{3} + \pi k}$ (wrong)

But none of the two last roots fits to the original equation. And I lost another 2 roots. Where is my mistake? Any suggestions will be greatly appreciated. Thanks for attention.

share|improve this question

2 Answers 2

up vote 3 down vote accepted

Just minor slippage. For example, from $\cos 2x=1$ you concluded that $2x=\pi k$. That is false, we need $k$ to be even: if for example $2x=\pi$, then $\cos 2x=-1$.

I don't understand your concern with $\frac{\pi}{3}$. It works.

share|improve this answer
    
yes, it works. Huge thanks to both of you. –  user907860 Feb 2 '13 at 4:03

If $\cos 2x=1\implies 2x=2n_1\pi,x=n_1\pi$

If $\cos2x=-\frac12=\cos \frac{2\pi}3\implies 2x=2n_2\pi\pm \frac{2\pi}3= \frac{2\pi}3(3n_2\pm1)\implies x=\frac\pi3(3n\pm1)$

If we compare these $x=n_1\pi,\frac\pi3(3n_2\pm1)$ with $x=k_1\pi,k_2\frac\pi3,$

the apparent mismatch is when $3\mid k_2$

But, in that case the result $k_2\frac\pi3 \in x=n_1\pi$ where $n_1,n_2,k_1,k_2$ are integers.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.